THE USE OF LANGUAGE GAMES TO INCREASE MOTIVATION IN LEARNING ISTIMÂ’ - Lubis, Ali Asrun; Yunaldi, Yunaldi; Yunita, Fitria Sari (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Factors that cause boredom in learning process are the lack of variety of methods, models, and media. An alternative to increase learning motivation in learning process is by using games. The main problem of this research is how to increase students motivation to make learning outcomes optimized. The purpose of this study was to increase students' motivation to learn istimâ' (listening) in Arabic is by using educational games. This study used classroom action research using a cycle model. The results of the study shows that educational games can increase students' learning motivation, shown by the comparison of initial motivation and after giving an action using educational games. The initial motivation data was in average 42.36%, in the category of low learning motivation, after giving an action in the first cycle it reached to an average 78.33%, high category, and increased in the second cycle with average 93.28%, very high category. The study concluded that educational games can increase motivation in learning istimâ' in Arabic.